2021
DOI: 10.3390/app112110478
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Relevant Concentrations of Triclosan Induce Cyto-Genotoxicity and Biochemical Alterations in the Hatchlings of Labeo rohita

Abstract: Xenobiotic Triclosan (TCS) is of great concern because of its existence in a variety of personal, household and healthcare products and continuous discharge in water worldwide. Excessive use of TCS-containing sanitizers and antiseptic products during the COVID-19 pandemic further increased its content in aquatic ecosystems. The present study deals with the cyto-genotoxic effects and biochemical alterations in the hatchlings of Labeo rohita on exposure to environmentally relevant concentrations of TCS. Three-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…Significant decrease in the intensity of these peaks after recovery may be linked with either oxidation of proteins under the influence of accumulated ROS or their metabolism to fulfil higher energy demand in the stressed hatchlings. In our previous studies (Sharma et al, 2021a;2021b), we observed a significant decline in protein content in the TCS exposed hatchlings and this directly supports the present observations. Similarly, altered intensity of amide A, amide I and amide II has also been reported in the TCS exposed embryos/larvae of four food fishes (Dar et al, 2022) and in liver, muscle, brain and kidney of arsenic exposed fingerlings of L. rohita (Palaniappan and Vijayasundaram, 2008a;Palaniappan and Vijayasundaram, 2008b;Palaniappan and Vijayasundaram, 2009a;Palaniappan and Vijayasundaram, 2009b).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Significant decrease in the intensity of these peaks after recovery may be linked with either oxidation of proteins under the influence of accumulated ROS or their metabolism to fulfil higher energy demand in the stressed hatchlings. In our previous studies (Sharma et al, 2021a;2021b), we observed a significant decline in protein content in the TCS exposed hatchlings and this directly supports the present observations. Similarly, altered intensity of amide A, amide I and amide II has also been reported in the TCS exposed embryos/larvae of four food fishes (Dar et al, 2022) and in liver, muscle, brain and kidney of arsenic exposed fingerlings of L. rohita (Palaniappan and Vijayasundaram, 2008a;Palaniappan and Vijayasundaram, 2008b;Palaniappan and Vijayasundaram, 2009a;Palaniappan and Vijayasundaram, 2009b).…”
Section: Discussionsupporting
confidence: 92%
“…It was performed by the protocol of Sharma et al (2021b). Cell suspension was prepared by homogenizing 10 hatchlings in 500 µl of phosphate buffer saline (7.4) followed by centrifugation at 500 × g for 10 min.…”
Section: Cell Viability Testmentioning
confidence: 99%
See 1 more Smart Citation
“…While their application contributes to increased food production, it is also linked to potential risks such as water body contamination and adverse health effects on non-target organisms [ 9 , 10 ]. Unsystematic and unabated use of these agrochemicals endangers the aquatic ecosystems in areas adjacent to agricultural fields, ultimately endangering non-target aquatic organisms [ [11] , [12] , [13] , [14] , [15] ]. Within this context, pesticides predominantly can be absorbed through fish gills, skin, or the digestive system, subsequently making their way to various tissues through the circulatory system [ [16] , [17] , [18] ].…”
Section: Introductionmentioning
confidence: 99%
“…As a response to mitigate the detrimental impact of xenobiotics on aquatic organisms, the exploration of additive-based treatments sourced from natural origins is progressively gaining prominence and attention [ [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. The worldwide exploration of the modulatory role of antioxidants found within phytochemicals, as a means to diminish free radical-induced damage, underscores the growing significance of this area of research [ 13 ]. In this context, recognised as “milk thistle” is Silybum marianum , a member of the Asteraceae family, which holds a significant status as a herb with remarkable antioxidant properties [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%